Three Lower Lip Sinuses with Congenital Bands Holding Upper and Lower Jaw Together in a Case of Bilateral Cleft Lip and Palate - B.K. Majumdar; Collin Roy; Siti Roy Chowdhury (Indian Journal of Plastic Surgery)
A case of congenital fibrous band holding upper and lower jaw together along with lower lip sinuses in a case of bilateral cleft lip and palate is presented.